2008
DOI: 10.2353/ajpath.2008.070324
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Defined T-Cell Responses to Cardiac Self Determine Differential Outcomes of Murine Dilated Cardiomyopathy

Abstract: Idiopathic dilated cardiomyopathy (DCM) is a disease of putative autoimmune origin that kills males at a twofold to threefold greater frequency than females. The reasons underlying these differential outcomes may be related to sex-divergent self-recognition. Here we examined sex-specific autoimmune responses to cardiac self and their impact on DCM development. We found that males immunized to the p406-425 peptide derived from mouse cardiac ␣-myosin heavy chain preferentially develop a predominant Th17 lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, future studies using von Frey filaments to assess the severity of response to mechanical stimulation (tactile allodynia) could be performed to compare values before immunization and progression over time. Further analysis using a device recently developed by our group, bladder sensory perception threshold [30], integrated with the Neurometer diagnostic neurostimulator (Neurotron, Baltimore, MD, USA), could be used to measure afferent sensory function as a phenotyping measure of pelvic pain in rmUPK2-immunized mice with EAC [18]. Overall, we have demonstrated the organ-specific autoimmune nature of rmUPK2-immunized mice with EAC and suggest this is a potentially useful model for the future investigation of pathogenesis and therapeutic intervention of IC/PBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, future studies using von Frey filaments to assess the severity of response to mechanical stimulation (tactile allodynia) could be performed to compare values before immunization and progression over time. Further analysis using a device recently developed by our group, bladder sensory perception threshold [30], integrated with the Neurometer diagnostic neurostimulator (Neurotron, Baltimore, MD, USA), could be used to measure afferent sensory function as a phenotyping measure of pelvic pain in rmUPK2-immunized mice with EAC [18]. Overall, we have demonstrated the organ-specific autoimmune nature of rmUPK2-immunized mice with EAC and suggest this is a potentially useful model for the future investigation of pathogenesis and therapeutic intervention of IC/PBS.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [11,12,17,18], to determine immunogenicity, inguinal and axillary lymph node cells (LNCs) were removed from 10 mice 10 d after immunization with rmUPK2 and cultured as a single-cell suspension in 96-well flat-bottom microtiter Falcon plates (BD Biosciences, San Jose, CA, USA) at 3 × 10 5 cells per well in Dulbecco modified Eagle medium (DMEM) (Mediatech CellGro, Herndon, VA, USA) with 10% fetal bovine serum (HyClone), 5% HEPES buffer, 2% L-glutamine, and 1% penicillin/streptomycin (Invitrogen Life Technologies) added. Then rmUPK2 and recombinant mouse anti-Müllerian hormone (AMH) (as a control) were added in serial 10-fold dilutions to triplicate wells with positive control wells containing 2 µg/ml antimouse CD3 (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…It is a primary indication for heart transplantation and is associated with high morbidity and mortality . The prevalence of DCM is estimated to be as high as 1/2500 adults, and it is reported to affect an estimated two to three times as many women as men . Moreover, approximately 20%‐50% of affected patients have a family history, suggesting that heredity is an important cause of this disease .…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic DCM represents the substrate for approximately 10% of sudden cardiac deaths in the adult population [3] and there was increasing evidence for the participation of cellular and humoral autoimmunity in the pathological process of DCM, such as antibodies directed against the second extracellular loop of β1‐adrenergic (β1) receptors, antibodies against muscarinic M2‐acetylcholine (M2) receptors and antibodies against the catalytic α‐subunit of sarcolemmal Na‐K‐ATPase, which were known to play a role in the pathophysiology of DCM [4–6]. Recent studies also showed that T cell was an important determinant in the development of idiopathic DCM [7]. Moreover, Yi et al.…”
Section: Introductionmentioning
confidence: 99%